Psychological Peculiarities of the Foreign Languages Maste-ring by the Primary School Children - Trigub, G. V. (Psychological Prospects Journal, 2011)
The article is devoted to the psychological peculiarities of foreign languages mastering by the primary school children.
Keywords: method skills memory peculiarity perception formation attention thinking